Menganalisis Ide-Ide dalam Memasarkan Produk dan Menggunakan Teknologi yang Efisien - Havit Rifai; Yula Yunita; Virny Maharani; Eloh Bahiroh (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to analyze various ideas in marketing products by utilizing efficient technology. In today's digital era, the use of information and communication technology is key in marketing strategies. This study uses a descriptive analysis method by collecting data from relevant literature and case studies of companies that have successfully implemented technology in marketing. The results of the study indicate that the use of social media, e-commerce, and data analytics are some effective strategies in increasing sales and expanding market reach. In the ever-growing digital era, companies must continue to innovate in their marketing strategies to stay competitive. This article analyzes various ideas in marketing products by utilizing efficient technology. The main focus is on the use of digital technologies such as social media, data analytics, and marketing automation to increase the effectiveness of marketing campaigns. In addition, this article also discusses the importance of understanding consumer behavior and market trends to develop targeted marketing strategies. By adopting efficient technology, companies can reach a wider audience, increase customer interaction, and ultimately, increase sales and customer loyalty.